(untitled) - Sommerville, Ian (Harlow, Eng, 2001)
The new edition of this best-selling book provides a comprehensive discussion of software engineering techniques and shows how they can be applied in practical software projects. This book features new coverage of the software process and software process technology, system integration, requirements management, and risk analysis, as well as new chapters on pattern-based reuse, distributed system engineering, and legacy systems. Sommerville has incorporated a more object-oriented approach in this edition—using UML and Java—and has removed much of the material on CASE, formal methods, and Ada, making the book more in tune with current technology and practice. A new discussion of professional ethics in the introduction helps to make readers aware of the responsibilities that come with engineering software. The sixth edition uses Java for all programming examples, and bases all design examples on UML notation. It includes new chapters on pattern-based reuse, distributed system engineering, and legacy systems, as well as new coverage of the software process and software process technology, system integration, requirements management, and risk analysis. This book is designed for readers needing a general introduction to software engineering (development, management, and evolution), especially with regard to system requirements engineering and critical systems.
Phân tích yêu cầu phần mềm,Nhập môn công nghệ phần mềm
Keywords: Software engineering,Kỹ thuật phần mềm